PRIMARY CARBONIFEROUS AND PERMIAN PALEOMAGNETIC RESULTS FROM THE YILI BLOCK (NW CHINA) AND THEIR IMPLICATIONS ON THE GEODYNAMIC EVOLUTION OF CHINESE TIANSHAN BELT - Wang B.; Shu L.; Chen Y.; Zhan S.; Faure M.; Cluzel D.; Charvet J.; Laurent-Charvet S. (My University, 2007)
In order to better understand the tectonic role of the Yili Block on the Paleozoic evolution of the Chinese Tianshan Belt, we performed a primary paleomagnetic study on Carboniferous and Permian rocks from different areas in the Yili Block, NW of China. More than 320 sedimentary and volcanic samples were collected from 39 sites. Except for the Ordovician samples showing a weak and unstable magnetic remanence, the majority of this collection presents characteristic remanent magnetization carried by magnetite and hematite. In the study area, though positive fold test has been observed on the Early Carboniferous rocks, a general re-magnetization of these rocks has been identified and attributed to the Late Carboniferous magmatism. Moreover, all Early and Late Carboniferous samples from the interior of the Yili Block yield stable and coherent magnetic directions with exhaustively reverse magnetic polarity. The Late Carboniferous (C2) is considered as the magnetic remanence age since these rocks are covered or intruded by synchronous magmatic rocks of the Yili arc, which lasted until to ~ 310 Ma. The C2 paleomagnetic pole is therefore calculated at 68.6°N, 290.6°E with A95 = 6.4° and n = 15. The Late Carboniferous rocks located close to a deformation zone present a consistent magnetic inclination but significant different declination with respect to other areas and are suspected to have probably experienced a local rotation. Although no fold test can be performed due to the monoclinal bedding, stable magnetic components are isolated from Late Permian (P2) red beds in the interior of the Yili Block with also a solo reverse magnetic polarity, the P2 paleomagnetic pole of the Yili Block has been, therefore, calculated from the characteristic remanent magnetization: 79.7°N, 172.0°E with A95 = 11.3° and n = 5. Keeping important uncertainties in mind, comparisons of the C2 and P2 paleomagnetic poles of the Yili Block with available coeval poles of Junggar, Tarim and Siberia indicate (1) no significant relative motion between the Yili and Junggar blocks since the Late Carboniferous, (2) no significant or weak latitudinal relative motion occurred since the Late Carboniferous among these blocks, but (3) the 46.2° ± 15.1° and the 31.6° ± 15.1° counterclockwise rotations of the Yili-Junggar blocks with respect to Tarim and Siberia took place during C2 to P2. These rotations are accommodated by the Permian dextral strike-slip faults along the northern and southern sides of Tianshan Belt and sinistral strike-slip faulting along the Erqishi Fault of Altay Belt, resulting in about 1000 km and 600 km lateral displacements in the Tianshan and Altay belts, respectively. © 2007.
Keywords: PALEOMAGNETISM; PALEOZOIC; ROTATION; STRIKE-SLIP FAULTING; TIANSHAN BELT; YILI BLOCK; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Permian; Палеозой::Пермская